Progressive damage and failure response of hybrid 3D textile composites subjected to flexural loading, part I: Experimental studies. (1st December 2015) - Zhang, Dianyun; Waas, Anthony M.; Yen, Chian-Fong
Abstract: This paper presents an experimental investigation of the deformation responses and failure mechanisms of hybrid 3D textile composites (H3DTCs) subjected to quasi-static three-point bending. The term "hybrid" refers to different constituent fiber tows, including carbon, glass, and Kevlar that are integrally woven into a single preform. Three different hybrid architectures, manufactured by varying the percentages and lay-ups of the constituent fiber tows, were examined to understand the effect of hybridization on the resulting performance enhancement, including the bending modulus, flexural yield stress, and strain to failure. All the architectures show a "plastic-like" nonlinear flexural response, indicating considerable damage tolerance and durability for this class of materials. It has been found that increasing the thickness of the specimens can increase the strain to failure in flexure. For an asymmetric H3DTC, which refers to an architecture that has carbon plies on one side and glass plies on the other (through-the-thickness), an increased flexural yield stress can be achieved by placing the glass on the side that experiences compressive straining in flexure, whereas the failure strain is reduced by placing the carbon on the side which experiences tension. Distributed matrix cracking was observed in regions of predominant tension through a digital image correlation (DIC) technique. Although the experimental results show architecture-dependent responses, fiber tow kinking, which develops on the compressive side of the specimen is determined to be a strength limiting mechanism for this class of materials subjected to flexural loading. The experimental results are subsequently used as a basis for developing a mechanics based multiscale computational model for H3DTC deformation, damage and failure response in flexure. Details of the modeling strategy and the development of damage and failure constitutive models are presented in Part II of this two-part sequence (Zhang et al., 2015).